The Management of large and massive rotator cuff tears- Current trends amongst UK shoulder surgeons - RG Hackney; Paul Cowling; M Ismail; M Javed; PG Conaghan; SR Kingsbury (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2018)
Background: Management of large and massive rotator cuff tears remains controversial. Such tears are often irreparable, and results of treatment are unpredictable. This study documents the current practice of orthopaedic surgeons in the British Elbow and Shoulder Society. Methods: A questionnaire was prepared pertaining to the management of large and massive rotator cuff tears with minimal degenerative changes in three age groups: Patients of 50 years (young), 65 years (still active), aged 75 years (elderly) were considered. Various risk factors for failure of repair were considered. Results: Physiotherapy and arthroscopic debridement were the most commonly selected management options in young and middle groups in cases of a large/massive rotator cuff tear. Patch repairs were offered by 30% of respondents overall. Latissimus dorsi transfer was utilised by 30%, 8% and 2% respectively in each age group. Reverse shoulder replacement was indicated by 8%, 36% and 76% respectively. Discussion: There was a marked inconsistency in the pre-op planning and number and choice of options between respondents. Most surgeons offered non-augmented repairs in a scenario where they admitted failure was likely. The need for a multicenter trial is widely recognised and 87% of respondents were willing to participate in such a trial.